Intravascular lymphomatosis in the central nervous system of dogs: Immunohistochemical investigation in two cases - Machado, Gisele Fabrino [UNESP]; Castro, Márcio B.; Melo, Guilherme D. [UNESP]; Ferreira, Wagner Luis [UNESP]; Aylon, Eliana G.; Alessi, Antonio C. [UNESP] (My University, 2011)
We report here two postmortem cases of dogs with intravascular lymphomatosis affecting the central nervous system. Intravascular lymphomatosis is represented by an exclusively intravascular proliferation of neoplastic lymphoid cells. To characterize the origin of the neoplastic cells, we have proceeded with immunohistochemical analysis to identify B and T lymphocytes and endothelial cells. The results showed predominance of cells from the T cell lineage, and no evidence of B cell origin was found. Few cells from one dog also exhibited cytoplasmatic staining for vimentin and Von Willebrand factor. Although in one case some immunophenotype diversity was observed, the massive presence of CD3 positive cells confirmed these neoplasms as intravascular lymphomatosis of T cell origin.
Keywords: Cell marker; Immunohistochemistry; Lymphoproliferative disorder; Neoplasia; Neuropathology; T cell; Canis familiaris